Introduction [in Advancing the climate and bioeconomy agenda in Africa for resilient and sustainable agrifood systems] - Yamdjeu, Augustin Wambo; Glatzel, Katrin; Tadesse, Getaw; Savadogo, Moumini (AKADEMIYA2063, 2024)
Taken together, long-term dynamics such as demographic changes, urbanization, and a continent-wide nutrition transition pose a complex set of challenges to African agrifood systems. These challenges are further compounded by the frequent and extreme weather events linked to the deepening climate crisis, whose effects range from prolonged droughts, floods, and disease outbreaks, to rising sea levels, increasing heatwaves, and changing rainfall patterns. Left unmitigated, the likely effects on agricultural yields and productivity, infrastructure, broader economic growth, and community livelihoods risk unraveling the progress made in improving food security and nutrition, as well as alleviating poverty. In one of the latest illustrations of climate change impacts across Africa, several thousand people lost their lives in Libya after torrential rain caused two dams to collapse in September 2023. The recent El Niño–induced droughts and floods across Southern Africa have led the United Nations and its partners to call for urgent action, as more than 30 million people across the region face the effects of severe drought. The consortium has warned that millions could be pushed into acute hunger unless support is urgently mobilized before the next lean season (WFP 2024). These shocks are seriously disrupting production cycles and hampering the ability of countries to guarantee food security for their populations.